Radiation-induced admicellar polymerization of methacrylate acid for pH responsive cellulose nanofibrils - Hakimi, Nik Muhammad Faris; Mohamad, Siti Fatahiyah; Al Edrus, Syeed Saifulazry Osman; Antov, Petar; Fatriasari, Widya; Abdan, Khalina; Lee, Seng Hua (Springer Science and Business Media B.V., 2024)
In this study, radiation-induced admicellar polymerization of methacrylic acid (MAA) onto the surface of cellulose nanofibrils (CNFs) was conducted. The aim of the study was to use radiation-induced admicellar polymerization of MAA to obtain pH-responsive CNFs. The chemical, physical, and morphological changes of CNF-grafted poly(methacrylic acid) (PMAA) were studied at various absorbed radiation doses (10–50 kGy) and MAA concentrations (0.5–1.5 M). In addition, the change in absolute zeta value of CNF-grafted-PMAA with different concentrations of PMAA grafted was measured at pH values varied from 3 to 11. The results show that 20 kGy is a sufficient gamma irradiation dose in the inert condition as proved by the highest carboxyl concentration obtained. Grafting was demonstrated by an FTIR band, specifically at 1689 cm−1, corresponding to the carbonyl stretching vibration of the carboxyl group. The cross-section of a single CNF showed an increment in diameter, with the increased amount of PMAA concentration. TGA analysis of dipole–dipole interactions and hydrogen bonding showed that admicellar polymerization was successful. Meanwhile, PMAA amorphous reduced the crystallinity index of CNFs. The absolute zeta value decreased from pH 3 to pH 9, then increased proportionally until reaching pH 11. This research shows that radiation-induced admicellar polymerization is a viable method for grafting nanosurfaces, and it can be applied to a wide variety of nanoparticles.